Germany [videorecording (DVD)]. (World, 2021)
"Germany is a nation-state in Central Europe that encompasses an astonishing variety of cultural and regional differences. It is the second-most populous country in Europe after Russia, and the most populous member state of the European Union. Discover this culturally rich and innovative country at the heart of Europe."